Description of The Level of Public Knowledge Related to The Scheduled Sludge Service Program at Perumda Tirtanadi - Yulia Khairina Ashar; Anggie Al-Qarana Savitri; Dian Permata Sari; Dita Aryza (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Waste water is one of the sanitation factors that is of concern to the Indonesian government. One of the environmental pollution that occurs is wastewater. The occurrence of wastewater pollution can cause media to cause various types of diseases. This study aims to find out how to describe the level of public knowledge about the L2T2 program (Scheduled Sludge Service) at PERUMDA Wastewater Marketing Branch. This research method is descriptive qualitative. The instruments used were interview guidelines and questionnaires given to 7 informants. The data collection technique used is the triangulation technique. This research was conducted in February 2023. The research location was taken at Perumda Tirtanadi Wastewater Marketing Branch on Jalan Tani & Jalan Rumah Sumbu. The results of this study are based on several informants saying that it is important to have this L2T2 program. Due to the blessings of this program, cleanliness in several disposal sites such as ditches and rivers has become cleaner. The conclusion of this study is the lack of public knowledge about this program, and the community does not want to pay a predetermined monthly rate and they do not want to damage the condition of their homes due to a control hole created. Suggestions from this research are the superiors of Perumda Tirtanadi should encourage more door-to-door outreach to the community so that later the community will better understand the benefits of disludging septic tanks.Keywords: Environment, Knowledge, Waste Water